Analysis of the reaction He++He+He→He+2+He - J. E. Russell (The Journal of Chemical Physics, 1985)
The Wigner–Keck Monte Carlo trajectory method is employed to calculate the rate coefficient k for He+ ions recombining in gaseous helium at temperatures in the range 80<T<320 K. The attractive (repulsive) He+2 interaction is approximated by the sum of a Morse (anti-Morse) potential and a term taking into account the long range ion–induced dipole interaction. The relevant three body interaction is represented by an expression that is, in effect, an approximation to a simple variational calculation. This expression depends on the same parameters that specify the He+2 interactions. A method is devised for sampling points on the Wigner–Keck surface that permits the determination of a value of k to within a statistical error of about 10% by computing less than 1600 trajectories, of which less than 500 represent actual formation of a He+2 molecule. The computed values of k are found to be in fair agreement with experimental results obtained by Biondi and his collaborators. The temperature dependence is reproduced rather satisfactorily, but the magnitude is 10% to 20% too low. The computed values of k are found to be fairly insensitive to reasonable variations in the behavior of the two and three body potentials. In particular, the results are found to be totally insensitive to the behavior of the three body potential if more than one of the internuclear separations are relatively small. It is also found that long range ion–induced dipole forces, while playing a very important role, do not appear to dominate the recombination process to quite the extent that had apparently been assumed in some previous investigations. The results generally support a model proposed by Mahan, who had suggested that charge transfer is the mechanism primarily responsible for the reaction. It is suggested that the remaining discrepancy with experiment might be largely due to the formation of highly excited quasibound states by inward tunneling through the rotational barrier, which is a mechanism that had originally been proposed by Dickinson et al. as the dominant one in He+ recombination. Some qualitative arguments are presented that indicate that this mechanism, which is not taken into account by classical trajectory calculations, might be less important than had originally been thought.